Differentiated thyroid carcinoma in children: Clinical characteristics and long-term follow-up - Tamam, Muge; Uyanik, Ercan; Edís, Nurcan; Mulazimoglu, Mehmet; Ozpacaci, Tevfik (World Journal of Nuclear Medicine, 2020)
Differentiated thyroid cancer (DTC) is rare in children, but it still remains the most common endocrine malignancy in children. The aim of this study was to analyze treatment response to radioactive iodine (RAI) therapy, clinical outcomes, recurrences, survival analysis, and long-term follow-up. We retrospectively reviewed the medical records of 43 pediatric patients (≤17 years of age) with DTC diagnosis after thyroidectomy who were treated with RAI. The follow-up protocol consisted of detailed clinical examination, testing of thyroid function, determination of serum thyroglobulin (Tg), and anti-Tg antibodies, and neck ultrasonography application. Forty-three pediatric patients (34 females and 9 males) treated with RAI for DTC in our institute. The median follow-up period was 54 months. The histologic classification was papillary thyroid cancer in 41 patients and the remaining 2 patients had follicular thyroid cancer. After the long-term follow-up, complete remission, partial remission, and recurrent-persistent disease were observed in 37 patients, 3 patients, and 3 patients, respectively. Among the series, 1 death occurred due to multiple metastases. The mortality rate is 2.56%. Total thyroidectomy followed by RAI appears to be the most effective treatment for patients with pediatric DTC in terms of reducing the rate of relapse and improving surveillance for recurrent disease.
Keywords: Clinical outcome; long-term follow-up; pediatric differentiated thyroid carcinoma; radioactive iodine therapy; recurrence; survival analysis